Effects of Sampling Context on Spontaneous Expressive Language in Males with Fragile X Syndrome or Down Syndrome - Kover, Sara T. (2012)
PURPOSE: This study examined the impact of sampling context on multiple aspects of expressive language in males with fragile X syndrome in comparison to males with Down syndrome or typical development. METHOD: Participants with fragile X syndrome (n = 27), ages 10 to 17 years, were matched groupwise on nonverbal mental age to adolescents with Down syndrome (n = 15) and typically developing 3- to 6-year-olds (n = 15). Language sampling contexts were an interview-style conversation and narration of a wordless book, with scripted examiner behavior. Language was assessed in terms of amount of talk, MLU of communication unit (MLCU), lexical diversity, fluency, and intelligibility. RESULTS: Participants with fragile X syndrome had lower MLCU and lexical diversity than participants with typical development. Participants with Down syndrome produced yet lower MLCU. A differential effect of context among those with fragile X syndrome, Down syndrome, and typical development emerged for the number of attempts per minute, MLCU, and fluency. For participants with fragile X syndrome, autism symptom severity related to the number of utterances produced in conversation. Aspects of examiner behavior related to participant performance. CONCLUSIONS: Sampling context characteristics should be considered when assessing expressive language in individuals with neurodevelopmental disabilities.